COMMUNITY PREPAREDNESS FOR NATURAL DISASTERS IN CIKAHURIPAN VILLAGE, LEMBANG DISTRICT, WEST BANDUNG REGENCY - Larasati, Andini; Aritonang, Admiral Nelson; Hekmatyar, Versanudin (Politeknik Kesejahteraan Sosial Bandung, 2025)
This study aims to determine the level of disaster preparedness among the community of Cikahuripan Village, Lembang Subdistrict, West Bandung Regency, in facing 4 natural hazards. A quantitative descriptive approach was used, applying the LIPI– UNESCO/ISDR (2006) instrument, which consists of four parameters: disaster risk knowledge, emergency response planning, early warning systems, and resource mobilization. A total of 98 respondents from all neighborhood units (RW) in the village were selected as the research sample. The results showed that the Community Preparedness Index (CPI) reached 74.2, which falls into the